Нанофотонний сенсор для визначення слідових концентрацій органічних канцерогенів в водних розчинах - Сушко, О. А. (My University, 2013)
This work considers a development of novel nanophotonic method of organic carcinogens detection such as polycyclic aromatic hydrocarbons in water solutions. The method constitutes a combination of electrochemical and electrochemiluminescence analysis with the application of nanomaterials and nanotechnologies for sensor’s electrodes modification.
Keywords: поліциклічні ароматичні вуглеводні; бензо[а]пірен; нанофотонний метод; електрохемілюмінесцентний аналіз; перенос електрона